A Case of Chronic Patellar Instability Following Failed Lateral Release - Schoell, Kyle; Bolia, Ioanna K; Wier, Julian; BS; Hasan, Laith K; Haratian, Aryan; BS; Weber, Alexander E; Hatch, George F (Archives of Clinical and Medical Case Reports, 2021)
Case: The patient is a 25-year-old female with trochlear dysplasia, native left knee lateral patellar instability and iatrogenic medial patellar instability from treatment prior to presentation. She had grade 3 cartilage loss on the majority of her patellar articular surface. She underwent concurrent medial and lateral patellofemoral ligament reconstruction, Fulkerson osteotomy, and osteochondral allografting of her entire patellar articular surface. After reconstruction she had no further instances of instability. Conclusion: Patients with trochlear dysplasia and patellar instability require correction of their abnormal osseous anatomy in addition to soft tissue reconstruction. Concurrent MPFL and LPFL reconstruction with Fulkerson osteotomy and osteochondral allografting of the patella can successfully treat cases of multidirectional patellar instability with a large associated patellar osteochondral defect.